Blended Learning between Team Games Tournament and Web-Based Module to Improve Students’ Competency of Light Vehicle Programs - Wijaya, Robby; Widiyanti, Widiyanti; Suhartadi, Syarif; Basyirun, Basyirun (Universitas Negeri Malang, 2019)
Education plays an important role in printing Human Resources (HR), includingvocational schools. Learning methods and the availability of learning resources becomes very important and needed. The existence of the internet needs to be utilized to create innovative and interesting learning. The research method used is Classroom Action Research (CAR) which aims to determine the effect of the implementation of the blended learning team games tournament (TGT) and the Web-Based Module as an Effort to Increase the Achievement of Student Competencies in the Light Vehicle Engineering Program. The study was onducted in class X TKR 1, SMKN 1 Singosari in the 2017-2018 school year as many as 32 students. The treatment is given consisted of Action 1and Action 2 by observing the activities of the teacher, students, and post-test scores. In the pre-action, the percentage of completeness obtained was 67.74% while the Minimum Completeness Standard was 75%. After action 1, the achievement of student competence reached 93.5% with an average value of 86.53. While in Action 2, student learning completeness was 87.09% with an average value of 81.3. From the two actions implemented, it is found that the average results are above the minimum standard of a predetermined value of 75. The application of blended learning can improve student learning outcomes because the learning process is more interesting, active and innovative. students are more enthusiastic and happy with the learning model. With the tournament, students are trained to be responsible, care for friends, study independently and compete healthily. The application of Blended Learning team games tournament (TGT) and Web-based modules are recommended to be applied to other subjects because it is proven to be able to increase the achievement of student competencies and to be creative, innovative and interesting method.